THE OCCUPATIONAL HEALTH COMPENSATION AT PT. TIRTA INVESTAMA AIRMADIDI (DANONE AQUA) - Sumarauw, Siska I.; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Compensation is the monetary benefit which is given to an employee or worker giving their services to an organization. Compensation includes components like salary, wages, bonuses etc. The main problem within the research is regarding health compensation within the workers of PT. Tirta Investama Airmadidi. With all the descriptions regarding the benefits of health compensation and regarding the way of how health compensation, it is important to know more about the implementation of health compensation. The purpose of this study is to find out health compensation given toward the workers, particularly workers of PT. Investama Airmadidi. This study uses a qualitative method and interview toward informants were conducted in order to gain information regarding the phenomenon. The findings of this study shows that health compensation constructed by 2 aspects which are amount of claim and motivated workforce have some affect in several aspects. Based on the result, the company is expected to improve the health compensation system in order to secure the safety of the employees, it can boost the morale of the company and will give good impact in the future such as high number of retaining good quality employees.Â Keywords: occupational health compensation, amounts of claims, motivated workforce